2022
DOI: 10.3389/fgene.2022.922382
|View full text |Cite
|
Sign up to set email alerts
|

Educational attainment and offspring birth weight: A bidirectional Mendelian randomization study

Abstract: Background: The association between educational attainment (EA) and offspring birth weight (BW) has been reported by several traditional epidemiological studies. However, evidence for this association tends to be mixed and confounded. This study aimed to investigate the causal association between EA of parents and offspring BW.Methods: Here, we carried out a two-sample bidirectional Mendelian randomization (MR) analysis to examine the causal association between EA of males (n = 131,695) and females (n = 162,02… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 50 publications
3
8
0
Order By: Relevance
“…While a previous MR study observed no association between genetically estimated HDL-C level and offspring birth weight, we observed a negative association; the discrepancy may be explained by our study using updated genetic datasets evaluating many more individuals. We found a positive association between genetically estimated BMI and the risk of gestational diabetes, preeclampsia, and birth weight, as previously observed . We also found that high genetically estimated BMI was associated with an increased risk of ectopic pregnancy, an association that was not present in a previous MR study by Rogne et al due to smaller sample size.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…While a previous MR study observed no association between genetically estimated HDL-C level and offspring birth weight, we observed a negative association; the discrepancy may be explained by our study using updated genetic datasets evaluating many more individuals. We found a positive association between genetically estimated BMI and the risk of gestational diabetes, preeclampsia, and birth weight, as previously observed . We also found that high genetically estimated BMI was associated with an increased risk of ectopic pregnancy, an association that was not present in a previous MR study by Rogne et al due to smaller sample size.…”
Section: Discussionsupporting
confidence: 89%
“…To our knowledge, only 1 previous MR study has considered the association between educational attainment and a pregnancy outcome. That study found higher genetically estimated educational attainment to be associated with increased birth weight .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, MR‐Egger regression was employed to detect horizontal pleiotropy among genetic variants. A regression equation intercepting zero or a nonsignificant p ‐value (>.05) for the intercept term implied the absence of average pleiotropic bias 18,20 . Additionally, we applied the MR pleiotropy residual sum and outlier (MR‐PRESSO) methods to identify any outlier SNPs potentially contributing to pleiotropy 21 .…”
Section: Methodsmentioning
confidence: 99%
“…A regression equation intercepting zero or a nonsignificant p-value (>.05) for the intercept term implied the absence of average pleiotropic bias. 18,20 Additionally, we applied the MR pleiotropy residual sum and outlier (MR-PRESSO) methods to identify any outlier SNPs potentially contributing to pleiotropy. 21 Finally, a leave-one-out analysis was performed to evaluate whether the MR results were strongly driven by a specific SNP.…”
Section: Sensitivity Analysesmentioning
confidence: 99%